Constituintes Químicos De Protium Paniculatum (Burseraceae) - Zoghbi, Maria das Graças Bichara; Siqueira, Jane Beatriz G.; Wolter, Esther Levy Aguiar; Pereira Júnior, Orlando Libório (Acta Amazonica, 1993)
á- e β-myrin (0,012%), β-sitosterol and stigmasterol (0.003%),3,3'-di-0-methylellagic (0.093%) acid were isolated from the bark wood of Protium paniculatum. The presence of 3.3',4-tri-0-methylellagic acid was postulate on the of mass spectral analyses.", 'en
Chemical Constituents of Protium paniculatum (Burseraceae)
Keywords: Burseraceae; Protium; Terpenoids', "3,3'-di-o-metilelagic Acid", "3,3'-4-tri-o-metilelagic Acid"]; Burseraceac; Protium; Terpenoídes', "ácido 3,3'-di-o-metilelágico", "ácido 3,3',4-tri-o-metilelágico"]